The infection–microbiome–immunity axis in bladder cancer: mechanistic insights and therapeutic perspectives - Pan, Shen; Cui, Wanlin; Lin, Jiaman; Wang, Zhujun; Li, Zhenhua; Liu, Bitian (Frontiers in Immunology, 2026)
Bladder cancer (BC) represents a paradigm of infection-associated malignancy in which microbial dysbiosis, immune aging, and tumor microenvironmental remodeling converge to shape disease progression. Increasing evidence highlights the dual role of the urinary and gut microbiota in modulating bladder carcinogenesis through infection-driven inflammation and immune dysfunction. Chronic exposure to uropathogens and microbial imbalance disrupts epithelial integrity, promotes extracellular matrix degradation, and reprograms local immune signaling, collectively fostering a tumor-permissive niche. Concurrently, immunosenescence exacerbates microbial persistence and impairs antitumor immunity, reinforcing a pathogenic feedback loop between infection and immune decline. This review integrates current insights from microbiome research, tumor immunology, and microbial pathogenesis to delineate the mechanistic continuum linking infection, dysbiosis, and immune remodeling in BC. Finally, we discuss emerging microbiome-targeted and immunomodulatory strategies aimed at restoring microbial–immune equilibrium and improving therapeutic efficacy. Together, these perspectives provide a refined conceptual framework for understanding infection-driven oncogenesis and guiding precision interventions in BC.